Limitations in current day lighting related solar concentration devices: A critical review - Abdul-Rahman, H.; Wang, C. (Academic Journals, 2010)
This study introduces the day lighting related solar concentration devices such as light pipes (or tubular daylight guidance systems), optical fibers for light transport, conventional solar concentrators and luminescent solar concentrators (LSC). The principles of study, advantages and disadvantages for application of these day lighting related devices have been explained. Daylight has a disadvantage of not being able to reach deeper areas in a building such as storerooms, basements and corridors and it also brings the heat gain with the light. Light pipes and optical fibers were expected to transfer daylight to unreached areas, but light pipes have their difficulties in wiring and the optical fiber needs a pointolite for the light transportation. Solar concentrators are only sensitive for the beam radiation and they function poorly in overcast sky conditions. Even under a clear sky condition, trackers are always needed for conventional solar concentrators. Static concentrators always come with a poor concentration rate without a tracker and the light concentrated by normal luminescent solar concentrators could not be transported by optical fibers to a remote place since the light produced by LSCs is not a pointolite. Future studies especially cross disciplinary researches on developing new solar concentration devices in mitigating those limitations as discussed in this study are highly recommended.